2018
DOI: 10.1029/2017jf004460
|View full text |Cite
|
Sign up to set email alerts
|

Annual Sediment Transport Dynamics in the Narayani Basin, Central Nepal: Assessing the Impacts of Erosion Processes in the Annual Sediment Budget

Abstract: Identifying the roles of erosional processes in the denudation of mountain ranges requires a better understanding of erosional sensitivity to climatic, topographic, or lithologic controls. We analyzed erosion in the Narayani River basin (draining central Nepal and presenting contrasted lithologic and geochemical signatures in its outcropping rocks and a wide variety of erosional processes and climatic conditions) to assess the relative contributions of erosion processes to the annual sediment export. By combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 121 publications
(214 reference statements)
5
36
1
Order By: Relevance
“…Limiting the water sampling to the top 30 cm slightly underestimates the average SSC in a channel cross section (and thus the suspended sediment load). However, we argue that the rating behavior does not significantly change compared to depthintegrated measurements (Morin et al, 2018).…”
Section: Suspended Sediment Monitoring In German Waterwaysmentioning
confidence: 60%
“…Limiting the water sampling to the top 30 cm slightly underestimates the average SSC in a channel cross section (and thus the suspended sediment load). However, we argue that the rating behavior does not significantly change compared to depthintegrated measurements (Morin et al, 2018).…”
Section: Suspended Sediment Monitoring In German Waterwaysmentioning
confidence: 60%
“…The Gorkha earthquake may also not have been representative, as it was relatively deep (15 km) and did not rupture the surface (Avouac et al, 2015). In contrast, paleo-seismological investigations have shown that large surface-rupturing earthquakes (> 100 km long) have occurred along the Himalayan range (Mugnier et al, 2013;Bollinger et al, 2014). Earthquakes shallower than the Gorkha event would likely produce stronger ground motions and thus trigger more landslides and also potentially more large landslides.…”
Section: The Contribution Of Earthquake-triggered Landslides To Long-mentioning
confidence: 99%
“…Studies of paleo-ruptures in central Nepal, constrained by historical damage or dated fault scarps, have revealed complex earthquake intervals (Mugnier et al, 2013;Bollinger et al, 2014Bollinger et al, , 2016. Specifically, data from historical reconstructions, accounting for blind ruptures, suggest that at least six large earthquakes affected central Nepal in the last ∼ 1000 years, possibly eight if we consider ruptures from eastern and western Nepal that may have propagated to central Nepal (Mugnier et al, 2013;Bollinger et al, 2016). However, these ruptures have poorly constrained magnitudes, varying from M w ∼ 7.5 to 8.5, and have uncertain return times (Mugnier et al, 2013).…”
Section: Spatio-temporal Frequency Of Landsliding For the Estimation mentioning
confidence: 99%
See 1 more Smart Citation
“…It enables a two-dimensional synoptic map of sediment concentration, flux, and grain-size distribution across morphologically complex river channels, where depth and flow velocity often show significant lateral variations ( Fig. 6) and where averaging across the channel Morin et al, 2018;Santini et al, 2019) would likely result in significant errors of the calculated sediment flux and mean composition.…”
Section: Model Descriptionmentioning
confidence: 99%